Uji kandungan boraks, formalin dan rhodamin B pada makanan jajanan mahasiswa - Nur Fauzia Asmi; Widya Lestari Nurpratama; Deni Alamsah (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: BPOM data for 2020 shows that there are snacks that use unsafe Food Additives (BTP), such as borax, formalin and Rodhamin B circulating in the community which can cause health problems such as kidney and liver failure and are carcinogenic. Identification of BTP content in the new normal era after the Covid-19 pandemic can help detect snacks that are dangerous and safe so that they can become preventive materials for the community.Objectives: analyzing the content of borax, formalin and rhodamine B in snacks.Methods: the design in this research is experimental. Tests for the content of borax, formalin and rhodamine B were carried out at the Chemistry Laboratory of the Suherman Medika University. The sampling technique was simple random sampling with the criteria of food and beverages that were purchased by many students so that 12 samples of snack foods and 3 samples of drinks were obtained. Data collection was carried out in November 2022. Qualitatively test the content of borax, formalin and rhodamine B using the brand testkid.id. Data analysis was carried out univariately, namely the percentage of food content containing borax, formalin and rhodamine B.Results: a total of 9 food samples (75%) contained borax and 7 samples contained formalin (58.33%) in snacks around the Suherman Medika University. The beverage samples showed that none contained the coloring agent rhodamine B. The types of food containing borax and formalin in this study were somay and cilok.Conclusion: there are snacks that contain borax which is marked by a brownish-red color change on curcumin paper, and formalin which is marked by a purple color change in the sample while rhodamine B is not found in drinks that are of interest to students.